Exposure to di-2-ethylhexyl phthalate (DEHP) increases the risk of cancer - Luchen Yang; Xiaoyang Liu; Zhufeng Peng; Zhenghuan Liu; Pan Song; Jing Zhou; Kai Ma; Yunfei Yu; Qiang Dong (BMC Public Health, 2024)
Abstract Cancer is a major socioeconomic burden that seriously affects the life and spirit of patients. However, little is known about the role of environmental toxicant exposure in diseases, especially ubiquitous di-(2-ethylhexyl) phthalate (DEHP) which is one of the most widely used plasticizers. Hence, the objective of this study was to assess the potential association between cancer and DEHP. The data were collected using the 2011–2018 National Health and Nutrition Examination Survey (NHANES) data (n = 6147), and multiple logistic regression was conducted to evaluate the association. The concentrations of DEHP were calculated by each metabolite and split into quartiles for analysis. After adjusting for confounding factors, DEHP was significantly associated with an increased risk of cancer prevalence, and the metabolites of DEHP showed similar results (OR > 1.0, p < 0.05). Simultaneously, the association remained when the analyses were stratified by age and sex, and the risk of cancer appeared to be higher in male patients. In addition, further analysis suggested that DEHP exposure obviously increased the risk of female reproductive system cancer, male reproductive system cancer, and other cancers (OR > 1.0, p < 0.05) but not skin and soft tissue cancer. DEHP exposure is associated with the risk of cancer, especially female reproductive system cancer, male reproductive system cancer and other cancers.